2021
DOI: 10.3390/ijerph18031309
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Workplace Environment That Affects Motivation of Japanese Dental Hygienists

Abstract: Dental hygienists are in high demand due to insufficient workforce and a lack of an effective reinstatement support system. We investigated the reasons for willingness to work by analyzing the survey results of the employment status of Japanese dental hygienists conducted by Japan Dental Hygienists’ Association. In total, we mailed 16,113 questionnaires to all members of the association (response rate 53.4%). We carried out statistical analysis to determine the specific items to improve the hygienists’ working… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Finally, another series of articles focused on various enablers or components of dental hygienist job/career satisfaction. This included two from Korea [ 76 , 77 ], and one each from Australia [ 78 ], Japan [ 79 ] and the USA [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, another series of articles focused on various enablers or components of dental hygienist job/career satisfaction. This included two from Korea [ 76 , 77 ], and one each from Australia [ 78 ], Japan [ 79 ] and the USA [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety about lack of skills and knowledge may not arise after becoming a dental hygienist, but rather before becoming a dental hygienist. Similarly, in surveys of dental hygienists in Japan, 30–47% of them also indicated a lack of their own skills as a barrier to returning to work [ 37 , 38 ]. Furthermore, these studies focused on Japan, and no reports from other countries were found in our literature review.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have reported that the work environment of Japanese dental hygienists must be improved [ 13 , 15 , 37 , 38 ]. According to the Global Gender Gap Report 2021, Japan’s overall score in 2021 on the Gender Gap Index was 120 out of 156 countries [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Directly the work environment will affect organizational culture (Buhori et al, 2019). As with Motivation, managing a workplace environment that is healthier, safer, and more comfortable is an integral part of maintaining employee motivation so that it can reduce the turnover of employees in the company (Yamamoto et al, 2021). H1 There is an influence of the work environment on Motivation.…”
Section: Work Environmentmentioning
confidence: 99%